2015
DOI: 10.1186/s12879-016-1394-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of animal bites and post exposure prophylaxis in rabies: A five year study in a tertiary care unit in Sri Lanka

Abstract: BackgroundRabies is a global problem which occurs in more than 150 countries and territories including Sri Lanka, where human deaths from rabies are in decline whilst resources incurred for prevention of rabies are in sharp incline over the years. In this backdrop, we aim to audit the post-exposure treatment (PET) in rabies and the pattern of animal bites in a tertiary care hospital in Sri Lanka.MethodsThis study was carried out at Teaching Hospital Peradeniya (THP), in the Central Province of Sri Lanka from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
13
2
1
Order By: Relevance
“…The present study shows that domestic animals contributed to 87% of the exposure. This finding is inconsistent with previous studies, which reported that stray and/or roaming animals accounted for most incidents, and is in line with other studies that indicated that domestic animals were responsible for most exposures . Due to the well‐implemented China Stray Pet Care Project and overcrowded cities, there are few stray animals in the streets and communities.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The present study shows that domestic animals contributed to 87% of the exposure. This finding is inconsistent with previous studies, which reported that stray and/or roaming animals accounted for most incidents, and is in line with other studies that indicated that domestic animals were responsible for most exposures . Due to the well‐implemented China Stray Pet Care Project and overcrowded cities, there are few stray animals in the streets and communities.…”
Section: Discussioncontrasting
confidence: 95%
“…Earlier studies on the epidemiology of animal bites in India, Iran, Ethiopia, Pakistan, Bhutan, and Spain reported that stray animals caused the overwhelming majority of animal bites. Several recent studies in India, Sri Lanka, and Nigeria indicated that domestic animals were responsible for most exposures. Some studies reported that animal bites were mainly provoked, while other studies indicated that most animal bites were unprovoked …”
Section: Introductionmentioning
confidence: 99%
“…In Kashmir, males usually go out more frequently for work or for social visits as compared to females. Most of the available literature on dog bites has reported a male predominance [13,14,[17][18][19][20][21][22]. The percentage of child victims varies across studies from 25% to 72% [13-20, 23, 24].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…2 Exposures recorded in Sri Lanka are mainly from domestic or stray animals with very little exposure from wild animals. 2 Therefore, elimination of rabies in the domestic and stray animal population would lead to a marked decline in the number of cases in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%